Marketing Strategy of Precious Metals from an Islamic Economic Perspective: A Study at the Sejati Baru Gold Shop in Balikpapan - Ahmad Syauqi; Asikin Nor; Ahmad Shamdani (Rihlah Iqtishad: Jurnal Bisnis dan Keuangan Islam, 2026)
This study aims to analyze the marketing strategies of precious metals implemented by Toko Emas Sejati Baru Balikpapan from the perspective of Islamic economics. The strategies in this research are examined using the 7P Marketing Mix approach (Product, Price, Place, Promotion, People, Process, and Physical Evidence), and are assessed based on Islamic principles such as honesty (ṣidq), trustworthiness (manah), justice (al-‘adl), and morality-based service. The research employs a descriptive qualitative method, with data collected through interviews, observation, and documentation. Key informants include the store owner, service staff, and customers. The data were analyzed using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The findings reveal that the marketing strategies Implemented by the store are not only business-oriented but also reflect the values of Islamic economics. The marketing practices are free from gharar (uncertainty), tadlis (fraud), and najasy (false bidding), while also providing muamalah education to consumers. Toko Emas Sejati Baru serves as a prime example of how Islamic business ethics can be integrated into daily marketing practices.